Analysis The Effect of Electronic Money Use on Velocity of Money: Evidence from Indonesia - Pambudi, Sufi Azhari; Mubin, M. Khoerul (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2020)
This study aims to examine the effect of electronic money transactions on the velocity of money in Indonesia. This study uses a quantitative research approach using quarterly time series data for the 2010q1-2018q4 period. Using variable velocity obtained from Gross Domestic Product (GDP) divided by M2, electronic money transactions, GDP per capita, and interest rates using the Error Correction Model (ECM) method. The results show that in the long run variable electronic money transactions, income levels and interest rates are significantly positive. In the short term, interest rates and income levels are significantly positive, while electronic money transactions only have a slight effect on the velocity of money in Indonesia.